2022
DOI: 10.1055/s-0042-1750103
|View full text |Cite
|
Sign up to set email alerts
|

Expanding Access to Microneurosurgery in Low-Resource Settings: Feasibility of a Low-Cost Exoscope in Transforaminal Lumbar Interbody Fusion

Abstract: Objectives Less than a quarter of the world population has access to microneurosurgical care within a range of 2 hours. We introduce a simplified exoscopic visualization system to achieve optical magnification, illumination, and video recording in low-resource settings. Materials and Methods We purchased a 48 megapixels industrial microscope camera with a heavy-duty support arm, a wide field c-mount lens, and an LED ring light at a total cost of US$ 125. Sixteen patients with lumbar degenerative disk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…is is consistent with the previous studies that have reported low complication rates for endoscopic spine surgery compared to open surgeries. [11,27,39,41,44] A recent clinical study [35] which aims to analyze the return to work and recovery time to narcotic independence following outpatient endoscopic decompression for contained lumbar herniated disc causing sciatica-type low back and leg pain, [29] Similarly, Giordan et al, [15], in their systematic review with meta-analysis (14 studies encompassing 600 patients), reported that about 85% of patients who underwent ELF for LFS had good outcomes with an overall intraoperative dural tear rate of 0.9%, whereas overall postoperative transient leg dysesthesia rate was 2.4% and overall same-level recurrent stenosis rate was 1.4%. However, other studies have reported mixed results with endoscopic surgery for LFS.…”
Section: Discussionmentioning
confidence: 99%
“…is is consistent with the previous studies that have reported low complication rates for endoscopic spine surgery compared to open surgeries. [11,27,39,41,44] A recent clinical study [35] which aims to analyze the return to work and recovery time to narcotic independence following outpatient endoscopic decompression for contained lumbar herniated disc causing sciatica-type low back and leg pain, [29] Similarly, Giordan et al, [15], in their systematic review with meta-analysis (14 studies encompassing 600 patients), reported that about 85% of patients who underwent ELF for LFS had good outcomes with an overall intraoperative dural tear rate of 0.9%, whereas overall postoperative transient leg dysesthesia rate was 2.4% and overall same-level recurrent stenosis rate was 1.4%. However, other studies have reported mixed results with endoscopic surgery for LFS.…”
Section: Discussionmentioning
confidence: 99%
“…We used a previously described device ( 13 ), this EX consists of a 48 megapixels 4K 1,080p industrial video microscope camera with a 1X-130X C mount lens to a cantilever. The portable stand allows manual positioning of the camera.…”
Section: Methodsmentioning
confidence: 99%
“…[43] is technology offers several advantages over traditional microscopes and is increasingly being utilized alongside endoscopic techniques for more precise and less invasive surgeries. [46] One of the key benefits of the exoscope is its flexibility in terms of positioning and angle of view. is is particularly advantageous in orbital tumor surgeries where the workspace is confined, and the need for precision is paramount.…”
Section: External Surgical Approachesmentioning
confidence: 99%